2009
DOI: 10.2164/jandrol.108.005959
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality Decline Among Men in Infertile Relationships: Experience Over 12 Years in the South of Tunisia

Abstract: Concerns about the worldwide decline in semen quality over the past 50 years are increasing. Western countries have shown a decline in semen quality. However, in non-Western countries studies are sparse. We investigated trends in semen parameters between 1996 and 2007 in the Sfax area of southern Tunisia in a sample of 2940 men in infertile relationships. Age at semen collection, duration of sexual abstinence, volume of seminal fluid, the sperm count, percentages of motile and morphologically normal spermatozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 39 publications
10
34
0
1
Order By: Relevance
“…35 Nevertheless, our results appear to be in keeping with the hypothesis advanced by Sharpe and Skakkebaek;36 that is, environmental factors during foetal, childhood/pubertal period or adult life, can have detrimental effects on spermatogenesis. The higher risk of testicular cancer and poor semen quality over the past decades has drawn attention to the possibility that environmental xenoestrogens may be implicated.…”
Section: Contribution Of Environmental Factorssupporting
confidence: 89%
“…35 Nevertheless, our results appear to be in keeping with the hypothesis advanced by Sharpe and Skakkebaek;36 that is, environmental factors during foetal, childhood/pubertal period or adult life, can have detrimental effects on spermatogenesis. The higher risk of testicular cancer and poor semen quality over the past decades has drawn attention to the possibility that environmental xenoestrogens may be implicated.…”
Section: Contribution Of Environmental Factorssupporting
confidence: 89%
“…The effects of age on fertility are real and may be greater than has been thought and it's well known that the fertility declines with age [22]. Previous studies documented that age is associated with diminished in semen volume, sperm count, sperm concentration, motility and morphology [38,39]. Similarly, we concluded that increasing age is associated with decreased seminogram and older men have lower semen volume and sperm parameters.…”
Section: C-a Comparison Of Semen Parameters and Mda Among Infertile Msupporting
confidence: 54%
“…Research articles on humans published in English from 1965 to 2015 were included in this report [23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). .…”
Section: Data Extraction and Data Anaysismentioning
confidence: 99%